Big stick energy - Bowen, Sarina (New York Legends hockey, 2026)
"A hockey team captain and a bubbly staffer mix business with pleasure when they start fake dating through the wedding season in this hot sports romance perfect for fans of Mariana Zapata and Elle Kennedy. Darcy Kendrick is used to putting out fires. As an overworked admin to a hockey team, she's seen it all. But nothing prepares her for accidentally DMing her very private, very NSFW fantasy to the subject of this fantasy: team captain Eric Tremaine. Nobody actually dies of embarrassment. Right? But when a wedding invite puts them on a collision course with her chaotic family and his emotionally fraught past, Eric suggests a plan: they fake-date their way through the "Wedding Experience." It's mutually beneficial. Totally strategic. And definitely not real. Except between mini tacos, slow dances and lingering glances, Eric starts to wonder if the sharp-tongued assistant with a bottomless to-do list might be the one person who truly sees him. And for Darcy? The fire in her heart might be the only one she can't put out. It's supposed to be fake. It's supposed to be temporary. So why is it so hard to walk away?"-- Provided by publisher.